2022
DOI: 10.3389/fmicb.2022.951857
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antimicrobial susceptibility of Pseudomonas spp. and Acinetobacter spp. from clinical samples at Jimma medical center, Ethiopia

Abstract: IntroductionPseudomonas aeruginosa (P. aeruginosa) and Acinetobacter baumannii (A. baumannii) can cause difficult-to-treat infections. We characterized molecular epidemiology of ceftazidime-resistant P. aeruginosa and carbapenem-resistant A. baumannii at a tertiary hospital in Ethiopia.Materials and methodsNon-fermenting gram-negative bacilli (n = 80) isolated from admitted patients were subjected for species identification by MALDI-TOF. Pseudomonas species resistant to ceftazidime or meropenem, and Acinetobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
3
6
3
Order By: Relevance
“…In this retrospective study, we analyzed the five-year antimicrobial resistance profiles of P. aeruginosa and Acinetobacter species with an emphasis on the prevalence and trends of carbapenem resistance at the Ethiopian Public Health Institute, Addis Ababa, Ethiopia. The prevalence of carbapenem-resistant Acinetobacter species in the current study was 61%, which is consistent with the findings of the study from Pretoria, South Africa (63%), 27 and Jimma, Ethiopia (56.4%), 25 however, it is higher than the findings of studies from Lusaka, Zambia (18.2%), 28 Switzerland (9.2%), 29 North-East, Ethiopia (34.5%), 18 Sidama, Ethiopia (9.9%), 22 North Gondar, Ethiopia (20.77%), 24 Northwest Ethiopia (33.3%), 17 and Dessie, Ethiopia (43.8). 16 The variation could be attributed to differences in study design, the number of isolates analyzed, the types of specimens considered, and the amount of data analyzed, as some studies only analyzed fewer data, while others analyzed a large amount of national antimicrobial resistance data, geographical differences, and antibiotic prescription policy differences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this retrospective study, we analyzed the five-year antimicrobial resistance profiles of P. aeruginosa and Acinetobacter species with an emphasis on the prevalence and trends of carbapenem resistance at the Ethiopian Public Health Institute, Addis Ababa, Ethiopia. The prevalence of carbapenem-resistant Acinetobacter species in the current study was 61%, which is consistent with the findings of the study from Pretoria, South Africa (63%), 27 and Jimma, Ethiopia (56.4%), 25 however, it is higher than the findings of studies from Lusaka, Zambia (18.2%), 28 Switzerland (9.2%), 29 North-East, Ethiopia (34.5%), 18 Sidama, Ethiopia (9.9%), 22 North Gondar, Ethiopia (20.77%), 24 Northwest Ethiopia (33.3%), 17 and Dessie, Ethiopia (43.8). 16 The variation could be attributed to differences in study design, the number of isolates analyzed, the types of specimens considered, and the amount of data analyzed, as some studies only analyzed fewer data, while others analyzed a large amount of national antimicrobial resistance data, geographical differences, and antibiotic prescription policy differences.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the overall prevalence of carbapenem-resistant P. aeruginosa was 22%, which is lower compared to the study from Dessie Comprehensive Specialized Hospital, Ethiopia (41.3%), 18 Jimma, Ethiopia (30%), 25 and Felegehiwot referral hospital, Ethiopia (45.5%). 17 The observed variation could be attributed to the fact that they only analyzed 46, 10, and 11 P. aeruginosa isolates, respectively, and additionally the differences in study design since these studies used specimens collected from single health facilities.…”
Section: Discussioncontrasting
confidence: 68%
“…From the result, P. aeruginosa accounted for 23.8% of all the isolates. Although there seem to be geographical differences in the proportions between the species earlier identified in other study, this observation is not parallel with report in Zaria were 10.5% and in North-eastern Nigeria 2.1% was reported [20,21], but strongly agrees with previous report of higher prevalence rate of 32.1% and 20.3% as published by Rajat et al [22] and Javiya et al [23] in Ahmadabad and Gujarat, India, 31.7% in Ethopia [24] and other studies that reported their presence in clinical samples in Germany and Tehran, Iran [25] respectively. It's worth noting that, the prevalence of P. aeruginosa isolates varied with clinical conditions and specimens while comparison of epidemiological data of enterobacteria as in this study might be difficult as there are other variables that influence the outcome of results such as, clinical specimens received for examination, studied population, type of hospitals and geographical locations.…”
Section: Discussionsupporting
confidence: 71%
“…This clone can be defined as a regional epidemic risk type for nosocomial healthcare. Some of the STs identified in this study have been previously described as new potential high-risk clones, including ST108 (Telling et al, 2018), ST179 (Moloney et al, 2020), ST253 (Fischer et al, 2020), ST260 (Martak et al, 2022), ST274 (Sewunet et al, 2022), ST348 (Dix et al, 2022), ST395 (Petitjean et al, 2017), ST446 (Pincus et al, 2019), ST463 (Hu et al, 2021), ST532 (Founou et al, 2020), ST699 (Rada et al, 2021 and ST773 (Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…Six global high-risk clones (ST111, ST235, ST244, ST277, ST298 and ST357) (Oliver et al, 2015) were identified in this study (Figure 2). In addition, 12 widely disseminated clones (previously reported as potential high-risk clones) were also identified, including ST108 (Telling et al, 2018), ST179 (Moloney et al, 2020), ST253 (Fischer et al, 2020), ST260 (Martak et al, 2022), ST274 (Sewunet et al, 2022), ST348 (Dix et al, 2022), ST395 (Petitjean et al, 2017), ST446 (Pincus et al, 2019), ST463 (Hu et al, 2021), ST532 (Founou et al, 2020), ST699 (Rada et al, 2021 and ST773 (Singh et al, 2021). We observed that several MDR clones identified in this study were related to highrisk clones and were thus part of the same subclade as them (Table 2).…”
Section: Subclade Of the High-risk Clones With Multidrug Resistancementioning
confidence: 97%